El mundo de la enfermera: "Uno aquí no se sienta". Contexto de los cuidados (2009)
ABSTRACT: To understand the context, goals and meanings that nurses give to their care roles. Methodology: qualitative investigation whose methodological approach was focused ethnography in nursing care to surgical patients in high complexity health institutes in Medellin, Colombia. The study is performed between 2005 and 2007. The data collection is done by means of participant observations and in-depth interviews to nurses. We carry out a total of 11 nurses’ interviews and observations of shifts changes, nursing rounds, medical rounds and patients discharge. We use an informed consent form that each interviewee signed. In open coded analysis we meticulously examin and compare searching, differences and similarities. Results: the findings make clear that nurses consider patient first of all as human beings and they believe that humanity is an essential component for those who you look after and is a value for those who provide care. Attention to every detail makes part of the nurse’s world in their care actions. They are responsible for everything in the service and it implies “having to have four eyes”. Conclusion: the nurses’ world, in the studied services, is characterized as a complex context that demands to be permanently attentive to multiple and simultaneous situations. In their own words is defined as “Here we never rest”.